Practical considerations for engaging staff in resource-constrained healthcare settings in implementation research: A qualitative focus group and consensus building study - Kelly A. Aschbrenner; Callie Walsh-Bailey; Meagan C. Brown; Tanveer Khan; Travis P. Baggett; Salene M.W. Jones; Douglas E. Levy; Lydia E. Pace; Jonathan P. Winickoff (Journal of Clinical and Translational Science)
Abstract